Posttraumatic Stress Disorder Diagnosis in Young Children With Burns. Issue 1 (January 2017) - Stoddard, Frederick J.; Sorrentino, Erica; Drake, Jennifer E.; Murphy, J. Michael; Kim, Abigail J.; Romo, Stephanie; Kagan, Jerome; Snidman, Nancy; Saxe, Glenn; Sheridan, Robert L.
Abstract : The primary aim of this study was to assess the prevalence of posttraumatic stress disorder (PTSD) in young children hospitalized for burns. A secondary aim was to assess partial PTSD in this population. PTSD diagnosis and symptoms were evaluated utilizing both the diagnostic interview for children and adolescents (DICA-P) module and the PTSD semistructured interview and observational report (PTSDSSI). PTSD symptomatology was assessed from parent interviews at 1 month after discharge from a major pediatric burn center. Four of the 42 participants who completed the DICA-P met full criteria for a diagnosis of PTSD (10%).Of the 39 who also completed the PTSDSSI, 1 (3%) met full criteria for PTSD diagnosis on that measure. Twenty-seven percentage of subjects met partial criteria on the DICA-P vs 16% on the PTSDSSI, without impairment. Furthermore, 67% of subjects met DICA-P criteria for the re-experiencing cluster and 54% met the PTSDSSI re-experiencing criteria. Although only a small percentage met full PTSD diagnostic criteria by either measure, a high percentage of young children with burns manifested some posttraumatic symptoms 1 month after discharge. Because PTSDSSI diagnosis is strongly linked to the diagnostic and statistical manual-5 (DSM-5) criteria for "PTSD in children 6 years and younger, " these results may offer clues to current diagnoses of PTSD in young children. Future research is needed to improve care by determining the risk factors and course of PTSD to further refine the diagnostic criteria for identifying children most in need of intervention, such as those hospitalized for burn injuries.